Law enforcement activities of the National Guard under martial law - I. V. Shmahailo (Law and Safety)
The National Guard was established at the beginning of Ukraine’s independence, but began its development only after 2014. Its functioning is due to the threat to public security and order of the state, in particular from the Russian Federation. Instead, the National Guard of Ukraine is a military formation that performs law enforcement functions and demonstrates its potential under martial law. Due to the specifics of the structure of this formation, the concepts of “law enforcement function” and “law enforcement activity” are studied. Law enforcement activities during martial law consist in carrying out actions by specially authorized bodies aimed at protecting the rights, freedoms and interests of citizens, the interests of the State and comply with the form specified in law, taking into account the effect of martial law.